Functional Income Distribution in a Small European Country: The Role of Financialisation and Other Determinants - Barradas, R.; Lagoa, S. (Dinâmia’CET-IUL Working Paper Nº 2015/04, 2015)
This paper makes an empirical analysis of the relationship between financialisation and the evolution of labour income share in Portugal from 1978 to 2012. We estimate an equation for the labour income share that includes standard variables (technological progress, globalisation, education and business cycle) and variables to capture the effect of financialisation. We formulate the hypothesis that the financialisation process may lead to a rise in the inequality of functional income distribution through three channels: the change in the sectorial composition of the economy (due to the increase in the weight of the financial activity and the decrease in government activity), the diffusion of shareholder value governance practices and the weakening of trade unions. Our results show that there is a long-term relationship between all variables and that the financialisation process indirectly affects the labour income share through its impact on government activity and trade union density. The paper also finds evidence supporting the traditional explanations for functional income distribution, namely globalisation, education and business cycle.